Zircon hafnium-oxygen isotope and trace element petrochronology of intraplate volcanic rocks from the Eifel (Germany) and implications for mantle versus crustal origins of Zircon Megacrysts - Schmitt, Axel Karl; Klitzke, Malte (Journal of petrology, 2017)
Abstract: Zircon megacrysts occur in association with mafic alkaline volcanic fields worldwide and have been used as indicators for the chemical characteristics of their mantle sources. However, their origins from magmas that are strongly undersaturated in zircon remain enigmatic. To resolve this conundrum, better constraints on the temporal and chemical relations between zircon megacrysts and associated mafic alkaline magmas are required. For six volcanoes from the West and East Eifel Volcanic Fields (WEVF, EEVF), Germany, we report concordant middle to late Pleistocene zircon megacryst crystallization ages from (230Th)/(238U) disequilibrium and disequilibrium-corrected 206Pb/238U geochronology, which generally agree with independently constrained eruption ages. Trace elements in Eifel zircon megacrysts indicate crystallization from highly fractionated melt pockets in which zircon competed with other accessory minerals e.g. apatite, titanite, pyrochlore) for incompatible elements enriched in residual melts, such as the rare earth elements, Th, and U. Eifel zircon megacrysts display systematic covariation between indices of differentiation (Eu/Eu*, Zr/Hf) and isotopic signatures of continental crustal contamination, revealing magmatic differentiation of parental mafic melts via coupled assimilation and fractional crystallization (AFC). Isotopic compositions of eHf and d18O in Eifel zircon megacrysts are consistent with mid- to upper-crustal AFC end-members, which are represented by xenolithic ejecta in WEFV and EEVF volcanic deposits, although not necessarily the same ones that yielded zircon megacrysts. Lower-crustal mafic granulites, by contrast, are a poor match for the isotopic trends displayed by the Eifel zircon megacrysts. These lines of evidence support that the zircon megacrysts in the Eifel originated from mantle melts that differentiated in the mid- to upper crust where they fractionated and partially solidified as syenitic intrusive bodies. Mafic magma recharge en route to the surface then scavenged and disintegrated syenitic rock fragments, in some cases liberating zircon crystals as the only recognizable survivors of their plutonic hosts. Zircon megacrysts in mafic alkaline magmas thus should be treated cautiously as tracers for mantle isotopic compositions. Mixing between mafic magmas and accessory-mineral rich syenites can selectively enrich incompatible trace elements, and potentially compromise the genetic interpretation of trace element patterns in mafic rocks.